Medicinal Values of Camel Milk - Kula Jilo (International Journal of Veterinary Science and Research - Peertechz Publications, 2016)
Camel milk differs from other ruminant milk as it contains low cholesterol, low sugar, high minerals,high vitamin C and higher protective proteins like lactoferrin, lactoperoxidase, Immunoglobulins and lysozyme. Camel milk lacks of β-lactoglobulin and used as an option for the individuals intolerant to lactose of cow's milk Camel's milk is unique in terms of antioxidative factors, antibacterial, antiviral, antifungal, anti-hepatitis, anti-arthritis, treatment for paratuberculosis, preventies aging, remedy for autoimmune diseases and cosmetics. Insulin in camel milk is safe and efficacious in improving longterm glycemic control in diabetic patient. Camel milk reduces autism symptoms in children. Lactoferrin has ability to inhibit the proliferation of cancer cell. Camel milk is rich in magnesium and zinc thus endowed antiulcer properties. Camel milk has high α-hydroxyl acids which are known to plump and smoothies the skin and also used to treat skin disorders such as dermatitis, Acne, Psoriasis and Eczema. Although camel milk has such values, it's less appreciated thus its consumption is restricted to pastoral area. Further studies should be conducted on the chemical composition and medicinal value of camel milk.